The Risk of Policy Tipping and Stranded Carbon Assets - Rick van der Ploeg; Armon Rezai (Center for Economic Studies and ifo Institute (CESifo), 2019)
If global warming is to stay below 2°C, there are four risks of assets stranding. First, substantial fossil fuel reserves will be stranded at the end of the fossil era. Second, this will be true for exploration capital too. Third, unanticipated changes in present or expected future climate policy cause instantaneous discrete jumps in today's valuation of physical and natural capital. Fourth, if timing and intensity of climate policy are uncertain, revaluation of assets occurs as uncertainty about future climate policy is resolved. E.g. abandoning climate policy plans immediately boosts scarcity rent, market capitalization, exploration investment and discoveries. To explain and quantify these four effects, we use an analytical model of investment in exploration capital with intertemporal adjustment costs, depletion of reserves and market capitalization, and calibrate it to the global oil and gas industry. Climate policy implements a carbon budget commensurate with 2°C peak warming and we allow for different instruments: immediate or delayed carbon taxes and renewable subsidies. The social welfare ranking of these instruments is inverse to that of the oil and gas industry which prefers renewable subsidy and delaying taxes for as long as possible. We also pay attention to how the legislative “risk” of tipping into policy action affects the timing of the end of the fossil era, the profitability of existing capital, and green paradox effects.
Keywords: D20; D53; D92; G11; H32; Q02; Q35; Q38; Q54; 330; fossil fuel; exploration investment; discoveries; stranded carbon assets; stock prices; irreversible capital; adjustment costs; policy tipping; botched climate policies